Konflik Batin Tokoh Ibu dalam Novel Ibuku (Tidak) Gila Karya Anggie D. Widowati: Studi Psikologi Kurt Lewin - Prikusuma, Athaya Ridha; Pamungkas, Onok Yayang (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
This research was motivated by the researcher's discovery that the mother character experienced a lot of inner conflict, which caused her mental disturbance. Inner conflict can be derived from the problems experienced by the mother character with other characters which ultimately have an impact on the way the mother character thinks and acts. The aim of this research is to explore the inner conflict of the mother character in the novel Ibuku (Not) Gila by Anggie D. Widowati from the perspective of Kurt Lewin's psychoanalysis. This research is a qualitative descriptive type using a literary psychology approach. The data collection technique used in this research is a documentary study technique. The documentary study technique was carried out by examining the novel Ibuku (No) Gila by Anggie D. Widowati, making it easier for researchers to connect it with the problems and objectives of the research. Researchers searched for and grouped quotes related to Kurt Lewin's inner conflict theory. Meanwhile, the data collection tool used in this research is the researcher himself as an instrument in the research. In this research, data cards are used to record the data to be analyzed, to make it easier for researchers to classify data according to the type of data. Apart from that, the tools used to collect data were pencils, pens, books, the novel My Mother (Not) Crazy by Anggie D. Widowati, and paper-bound sticky notes